The Implementation of Regional Autonomy Principles In Local Government Administration In Mamuju Regency, West Sulawesi - Muhammad Taufan, Putra (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
Regional autonomy is an important principle in Indonesia’s governmental system that aims to provide greater authority to local governments in managing their own administrative affairs and promoting regional development. This study examines the implementation of regional autonomy principles in the administration of local government in Mamuju Regency, West Sulawesi. The objective of this research is to analyze how regional autonomy has been implemented by the local government and to identify the challenges faced in its implementation. This study employs an empirical legal research approach with a qualitative method. Data were collected through interviews with government officials, analysis of legal documents, and observation of administrative practices within the local government institutions in Mamuju Regency. The findings indicate that the implementation of regional autonomy in Mamuju Regency has generally been carried out in accordance with national regulations, particularly in the areas of public service delivery, policy implementation, and local development planning. However, several challenges remain, including limited human resources, bureaucratic constraints, and coordination issues between the central and local governments. These challenges affect the effectiveness of policy implementation and the realization of good governance at the regional level. Therefore, strengthening institutional capacity, improving administrative professionalism, and enhancing coordination between levels of government are necessary to optimize the implementation of regional autonomy in Mamuju Regency. This research contributes to the understanding of how regional autonomy operates at the local level and provides recommendations for improving governance practices in regional administrations.